SUNDRAWING SEBAGAI TEKNIK EKSPERIMENTASI FOTOGRAFI - astiti, anin (Acintya, 2019)
AbstractThe sundrawing technique has been done by artists or photographers in photography in the 19th century. In the following years, they did something related to the making of photography. The practicality can be synergized with the standards in this study so that the tools used to make photograms can be done outdoors, using sunlight. For this reason, the process of making these tools is a process, which will be described in the inovated method.The sundrawing technique is a technique of exposing paper or light sensitive media using sunlight. Sundrawing in this case the author uses to realize a photogram that can be done outside the dark room, by utilizing sunlight, so it will be like the shooting process with conventional cameras in general. The main thing that must be done is to make a device in the form of a photogram camera which is then equipped with a lightproof bag / changing bag that is useful for removing paper from a photogram camera. By using the changing bag, there is no need for a dark room to enter and replace paper in the photogram camera.Keywords: sundrawing, experimentation, sun, photogram.